Spotedness of most active flare stars detected by TESS - Akopian, A. A.
A new method has been proposed to determine the coverage of starspots by using periodic functions related to flare frequency. The distribution of starspots on flare stars is modeled through a von Mises circular distribution, with parameters derived from the corresponding flare frequency function. Estimates of spot coverage for the stars studied have been obtained.
Keywords: Stars